The effect of phase transition of crednerite/delafossite CuMn 1− x Cr x O 2 on optical, thermal, and power factor properties - Pornjuk Srepusharawoot; Wattana Kosalwat; Chesta Ruttanapun (Journal of the American Ceramic Society, 2021)
Abstract This study aims to investigate the effect of the phase transition of CuMn 1− x Cr x O 2 compound on the Jahn–Teller effect which in turn affects the optical, thermal, and thermoelectric power factor properties. The CuMn 1− x Cr x O 2 samples were synthesized by a solid‐state reaction method. The ab initio computation was applied to evaluate the electronic and optical properties in order to confirm the experiment data. The appearance of the phase transition from crednerite CuMnO 2 to delafossite CuCrO 2 was confirmed by X‐ray diffraction (XRD) and the ab initio computation through displaying the mixed crednerite/delafossite phase; and, the existence of the Jahn–Teller effect was confirmed by the X‐ray photoelectron spectroscopy (XPS) technique exhibiting the occurrence of mixed‐state Mn 3+ /Mn 4+ ions. The results obtained from XRD, XPS, and the ab initio computation implied the decrease of the Jahn–Teller behavior with increased x content under the influence of the phase transition from the crednerite phase to the delafossite phase of CuMn 1− x Cr x O 2 . Surprisingly, the Jahn–Teller distortion reduction caused an increase in the energy gap of the optical property, electrical resistivity, and activation energy in thermally activated band conduction. The effect suffered the specific heat behavior by being separated into two groups of crednerite and delafossite, and enhanced the small polaron behavior by increasing the activation energy of thermally activated band conduction. The phase transition reduced the results of thermal conductivity, thermopower, and thermoelectric power factor properties. In other words, the effect of the phase transition from the crednerite CuMnO 2 phase to the delafossite CuCrO 2 phase on CuMn 1− x Cr x O 2 compound reduced the Jahn–Teller effect with increased Cr content which in turn caused changes in the optical, thermal, and thermoelectric power factor properties. The effect of the phase transition is advantageous for the improvement of material properties.
Keywords: Copper-based nanomaterials and applications; Electronic and Structural Properties of Oxides; ZnO doping and properties